The Effect of Empowerment, Work Environment and Work Motivation on Satisfaction of Credit Union Employees - Hanna Meilani Damanik; Musran Munizu; Slamet Riyadi; Abdurohim; Ilham (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This research was conducted at one of credit union in Indonesia. Using the saturated sample method, 80 people participated in this investigation. Interviewing and distributing questionnaires were used to obtain the data, which was then analyzed using multiple linear regression techniques and data processing with SPSS 23. Multiple linear regression analysis was the technique employed for data analysis. The investigation carried out revealed that the variables of the work environment, work motivation, and human resource empowerment have a substantial impact on job satisfaction.